Penggunaan Media Pembelajaran Monopoli Terhadap Kemampuan Literasi Numerasi Siswa Kelas IV Sekolah Dasar Tanwirul Afkar - Indirianisa, Vita; Nur Oktaviani, Rizka (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe the use of monopoly learning media on the numeracy literacy skills of grade IV elementary school students and to describe the numeracy literacy skills of grade IV elementary school students after using monopoly learning media. This study uses 5 indicators to obtain maximum research results, the 5 indicators are using symbols and numbers in mathematics, analyzing information displayed in the form of graphs, tables, and charts, problem solving skills, learning media, and the advantages and disadvantages of monopoly learning media. The method used in this study is qualitative through a phenomenological approach. There are several data collection techniques used in this study, namely observation, interviews, and documentation. The instruments used are observation sheets and interview sheets with informants. Then the data analysis is carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the use of monopoly learning media on numeracy literacy skills has been carried out very well and the numeracy literacy skills of grade IV students, namely 12 students who have reached 4 indicators, but only 2 students have not reached the indicator because students are not yet fluent in reading and understanding story problems on the material of multiplication of whole numbers.